Odpowiedzi

2010-02-07T15:22:43+01:00
A) 2x-y=5
3x=y-6

y=2x-5
3x=2x-5-6
x=-11
y=-22-5=-27

b) 7x-y+17=0
5x+6y=8

y=7x+17
5x+6(7x+17)=8
47x=-94
x=-2
y=3

c) y-2x=6
y=3+x

6+2x=x+3
x=-3
y=0
1 1 1
Najlepsza Odpowiedź!
2010-02-07T15:25:36+01:00
A)
2x-y=5
3x=y-6

y=2x-5
3x=2x-5-6

y=2x-5
x=-11

y=2*(-11)-5
x=-11

y=-22-5
x=-11

y=-27
x=-11
b)
7x-y+17=0
5x+6y=8

y=7x+17
5x+6(7x+17)=8

y=7x+17
5x+42x+102=8

y=7x+17
47x=-94

y=7x+17
x=-2

y=7*(-2)+17
x=-2

y=3
x=-2

c)
y-2x=6
y=3+x

y=3+x
3+x-2x=6

y=3+x
-x=3

y=3+x
x=-3

y=3+(-3)
x=-3

y=0
x=-3
4 1 4